Topics in modal analysis & testing. proceedings of the 34th IMAC, a conference and exposition on structural dynamics 2016 /: proceedings of the 34th IMAC, a conference and exposition on structural dynamics 2016. Volume 10 : (2016) - Unknown
No abstract available